(untitled) (Research, Society and Development, 2020)
To analyze the benefits of Integrative and Complementary Practices in labor.This is an integrative review. Data collection was carried out in the months of February and March 2020 in the lilacs, Bdenf, Scielo and Medline databases. Primary studies that answer the research question, in English, Portuguese and Spanish, and published between 2006 and 2019, were included, and 2006 is justified as the year of implementation of the PIC Policy in Brazil. Review studies, unavailable studies, duplicates, thesis-type documents, monographs and manuals were excluded. The initial sample of 224 studies was obtained. After reading the titles and abstracts, 10 studies were included in the final sample. It was possible to observe that Integrative and Complementary Practices - PICs were most used in the active phase of labor. , reduced labor time, improved comfort, reduced perineal trauma, pressure from uterine contractions and reduced stress, calm, relaxation, concentration and courage and pain control for women. Emphasize the importance of nurses seeking qualification in the area in order to provide differentiated and quality care, not only in obstetrics, but in other areas of nursing practice. It made the development of research in the area fundamental, an end of testing through clinical trials and the effects of possible PICs.